Study of Ship Loading and Unloading Methods to Improve Productivity at Tanjung Perak Port Surabaya - Saputra, Toto Dwijaya; Prawirosastro, Carlos; Marsudi, Sugeng (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2024)
The loading and unloading process of ships, known as stevedoring, is a critical operation in ports that significantly affects the efficiency of cargo handling and port operations. This study aims to analyze the stevedoring methods used in Tanjung Perak Port, Surabaya, to enhance productivity. A qualitative approach was employed, including observation, interviews, and document analysis. The findings reveal that conventional methods still dominate stevedoring activities, with limited utilization of modern techniques. Factors such as coordination among personnel and infrastructural limitations contribute to delays and inefficiencies. Comparatively, modern methods demonstrate higher productivity. Recommendations include the increased use of modern methods, infrastructure enhancements, improved coordination, and continuous evaluation and improvement. Implementing these recommendations is expected to improve stevedoring productivity in Tanjung Perak Port and optimize overall port operations.